Here's the completed table with the appropriate exponent rules for each expression:
| Expression | Exponent Rule | |--------------------------------------|-----------------------------------------| | \((16^3)^9 = 16^{27}\) | Power Rule | | \(\frac{11^{80}}{11^{22}} = 11^{58}\)| Quotient Rule | | \(\frac{6^{-12}}{9^{-15}} = \frac{9^{15}}{6^{12}}\)| Negative Integer Exponent Rule |
Explanation:
- Power Rule states that \((a^m)^n = a^{m \cdot n}\).
- Quotient Rule states that \(\frac{a^m}{a^n} = a^{m-n}\).
- Negative Integer Exponent Rule states that \(a^{-m} = \frac{1}{a^m}\) and can also be applied to help convert the expression to a more simplified form.
Let me know if you need any further assistance!